CHАLLENGES AND SOLUTIONS IN MODERN EDUCATION: BRIDGING THE GAPS FOR A MORE INCLUSIVE AND EFFECTIVE LEARNING SYSTEM - Laylo Turaboyeva; Durdona Khamidova (Western European Studies, 2025)
The modern education system serves as a fundamental pillar of societal progress, equipping individuals with the knowledge and skills necessary for personal and professional development. However, as technology advances and global demands shift, education faces numerous challenges that hinder its effectiveness and inclusivity. This article explores the various challenges facing the modern education system, including technological disparities, curriculum relevance, mental health issues, and the need for teacher training. It also presents potential solutions to these challenges, emphasizing the importance of adaptability, inclusivity, and mental health support in educational practices. The findings highlight the necessity for a holistic approach to reforming education to meet the needs of diverse learners
Keywords: educational challenges; practical learning